IMPROVEMENT LEGAL ASPECTS AND COMPLETENESS OF DOCUMENTATION USING RECORD: A REPORT OF STUDY: DOI: https://doi.org/10.35654/ijnhs.v1i2.46 - Rr.Tutik Sri Hariyati; Krisna Yetti Malawat; Retno Purwandari; Effy Afifah (International Journal of Nursing and Health Services (IJNHS), 2018)
Background: Completeness of documentation as a legal aspect and proof a nursing activity. Nothing documentation means nothing activity.Objective: The Purpose of research to identify the legal aspect and completeness of nursing documentation after applying electronic nursing documentation. Methods: Report study approach and using pre and post-test with the control group. Thirty Four documentation collected using consecutive sampling on one-week observation before and after using electronic nursing information. The research compared the legal aspect and completeness of data conducted before and after the implementation of the new system.Results: The study showed improvement of the legal aspects increased by 50% (4,40 to 8,00) and completeness documentation by 10.39% (43,00 to 49,00) after used of a system. Conclusion: Nursing Electronic Documentation improved legal aspect, completeness nursing and enhance the quality of nursing care. Recommendation: Electronic nursing documentation can be done to support and increase the quality of nursing.